2008
DOI: 10.1021/la800397f
|View full text |Cite
|
Sign up to set email alerts
|

Water Properties in the Super-Salt-Resistive Gel Probed by NMR and DSC

Abstract: The so-called "super-salt-resistive gel", or poly(4-vinylphenol) (P4VPh) hydrogel, of different water contents ( H = 97-51%) was prepared by cross-linking with different amounts of ethylene glycol diglycidyl ether. 1H NMR spectroscopy was used to investigate the dynamic properties of water in the gel samples in terms of the spin-spin relaxation. The T2 values in those hydrogels were analyzed by assuming a two-component system, namely, T 2(long) and T2(short), and their fractions were obtained. In the higher wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
(43 reference statements)
3
14
0
Order By: Relevance
“…Several methods were previously applied to determine the different types of water in hydrogels including NMR [14,15,16], dilatometry, conductivity measurements and thermal analysis [10,17,18 Different properties of hydrogels (such as oxygen permeability, the rate of drug release and release mechanism, etc.) can be adjusted by changing the water content in hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods were previously applied to determine the different types of water in hydrogels including NMR [14,15,16], dilatometry, conductivity measurements and thermal analysis [10,17,18 Different properties of hydrogels (such as oxygen permeability, the rate of drug release and release mechanism, etc.) can be adjusted by changing the water content in hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…The problem here is to identify which solvation and polymer-polymer interaction are mainly responsible for a swelling and a deswelling. Some hints are available from our previous findings; NMR and IR studies strongly suggested that hydration of P4VPh in hydrogel phase is specifically stabilized only when the acidic proton of the phenol OH is least consumed by crosslinking and sufficiently available for hydration [38,39]. According to the water band analysis of the IR spectra, water HB strength proved to be comparable to or higher than those in bulk water.…”
Section: Figmentioning
confidence: 78%
“…In a similar way, theπ-HBH is stabilized by cations because the acceptability of water protons, or AN of water, may be enhanced via ionic hydration. These stabilization schema have been, in fact, supported by different kinds of experimental data, such as ab initio calculation for the HBH to the phenol's acidic proton [37], T 2 values of water proton from NMR measurements for the hydrogel [38], and analysis of water and hydrations of the polymer segment in gel phase by FT-IR spectroscopy [39].…”
Section: Introductionmentioning
confidence: 98%
“…It is clear that if the interactions between water and the polymer matrix are getting stronger, the crystallization temperatures will be decreasing. The non-freezable bound water absorbed in polymer does not crystallize as a typical exothermic peak, even when the swollen sample is cooled down to −70°C ( 16 ).…”
Section: Resultsmentioning
confidence: 99%